The king's daughter [videorecording (DVD)] - Brosnan, Pierce; Scodelario, Kaya, 1992-; Walker, Benjamin, 1982-; Schreiber, Pablo; McIntyre, Vonda N. (Universal, 2022)
In 1684 France, Louis XIV, the Sun King, is the most powerful and influential monarch on the planet. But his birthday is approaching along with a rare solar eclipse and he's worried about the future of France. His spiritual advisor, Pr̈e La Chaise, comforts him, while his physician, Dr. Labarthe informs him that scientists believe mermaids contain a life force that grants immortality. Louis XIV's quest for immortality leads him to capture a mermaid's life force, but his immovable will is challenged when his long-hidden illegitimate daughter forms a bond with the magical creature.